(3eHGOF eMGSHI GdJcGdja (B/s - (3GdQLHj, eMeO JjSjQ YHO GdMcjes ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2004)
(3GdJYQja HeMGSHI GdJcGdja hCgejJgG(B- (3WHjYI hJUfjaGJ GdJcGdja(B- (3eMGSHI GdeQGMd GdEfJGLjI(B- (3GdJGda hGdaGbO hGdhMOGJ GdeYjHI hGdNQOI(B- (3GdJcGdja GdUfGYjI ZjQ GdeHGTQI(B- (3JcGdja GdefJLGJ GdQFjSjI hGdefJLGJ GdaQYjI(B- (3WQb JMejd GdJcGdja GdcdjI hGdeJZjQI(B- (3GdJcGdja GdeYjGQjI ddehGO hGdGLhQ hGdGYHGA GdEVGajI(B- (3GdJcGdja GdeYjGQjI hGdOhQI GdeMGSHjI(B-(3ehGVY NGUI aj JMdjd GfMQGaGJ GdJcGdja(B- (3JMdjd GfMQGaGJ GdEjQGOGJs
(3GdeQGLY U(B.473s
Keywords: (3GdeMGSHIs; (3eMGSHI GdJcGdjas